A polynorbornene anion exchange membrane and preparation method thereof
By introducing phenyl ether structure and piperidine cations into the polynorbornene-based polymer of the anion exchange membrane, the problem of easy destruction of the anion exchange membrane in an alkaline environment is solved, the membrane stability and high ion conductivity are achieved, and the battery performance is improved.
Patent Information
- Application Number
- CN202310152225.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-23
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2043-02-23
AI Technical Summary
The existing anion exchange membranes are easily destroyed in an alkaline environment, resulting in short service life and high cost, and insufficient dimensional stability and alkaline stability, affecting battery performance.
Polynorbornene-based polymers are used as the main chain, and by introducing phenyl ether-containing structures and piperidine cations into the side chains, a hydrophobic-hydrophilic phase separation structure is formed, enhancing the basic stability and ion conduction ability of the membrane.
The stability and high ion conductivity of the anion exchange membrane in an alkaline environment are achieved, which extends the service life of the membrane, reduces production costs, and improves battery performance.
Smart Images

Figure CN116284916B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of anion exchange membrane preparation, and relates to a novel polynorbornene anion exchange membrane and a preparation method thereof. The polynorbornene anion exchange membrane prepared by the invention is suitable for alkaline fuel cells and water electrolysis devices. Background Art
[0002] Anion exchange membrane (AEM) is an important component in alkaline fuel cells and water electrolysis devices, which can separate anions and cations and conduct OH - The role of anion exchange membrane OH - The conductivity and alkaline stability directly affect the performance of battery devices.
[0003] For example, the commercial Sustainion X37 anion exchange membrane (CAEM) has a high ion exchange capacity and good ion conductivity, but it is easily damaged by an alkaline environment, so its service life is not long, and its cost is higher than that of a cation exchange membrane of the same level.
[0004] At present, anion exchange membranes are still in the research stage, mainly focusing on the problems of poor dimensional stability and alkaline stability of anion exchange membranes, and improving the comprehensive performance of membranes by controlling the balance between dimensional stability and alkaline stability of anion exchange membranes. On the one hand, the dimensional stability of ion exchange membranes is closely related to the water absorption and swelling degree of the membrane itself, which has an important influence on ion conductivity; on the other hand, anion exchange membranes need to work in an alkaline environment. To improve the alkaline stability of the membrane, it is necessary to start from the membrane structure and adjust the monomer ratio and the type and number of functional groups in the polymer membrane so that it is not easily destroyed in an alkaline environment, thereby extending the service life of the membrane.
[0005] The polymer backbone of anion exchange membranes is mainly divided into ether-containing backbones and ether-free backbones. Generally speaking, ether-containing backbones are simple to synthesize, but the ether bond is easily affected by OH in an alkaline environment. - Therefore, its alkaline stability is poor, which seriously affects the service life of the membrane. Therefore, the ether-free main chain has attracted more attention from researchers.
[0006] Currently, the most studied ether-free main chains are polyphenylene and olefin polymers. The membrane structure of these polymers is relatively stable in an alkaline environment and has good chemical stability. However, the polymerization conditions of the two are relatively harsh and the degree of polymerization of the polymers is difficult to control, which means that the actual polymerization ratio of the polymer monomers is difficult to stably regulate.
[0007] As one of the important parameters for evaluating the performance of anion exchange membranes, ionic conductivity is seriously affected by the cationic functional groups in the membrane. Among the many types of cationic functional groups, 6-azaspiro[5.5]undecane (ASU) and N,N-dimethylpyrrolidinium (DMP) cations can stably exist in alkaline environments for a long time, but the synthesis process is complicated and the cost is high. Therefore, these two types of cations are not suitable for large-scale commercial applications. The stability of piperidine cationic functional groups is second only to ASU and DMP, and its synthesis process is simple, making it an ideal cationic functional group for anion exchange membranes.
[0008] Therefore, under the premise of ensuring the important property of ion conductivity, taking into account the alkaline stability and dimensional stability of the polymer, norbornene polymers perfectly meet the requirements for the main chain of anion exchange membranes, and their side chain structures are easy to modify, which facilitates the introduction of cationic functional groups; and piperidine cationic functional groups have high ion exchange capacity and usually exhibit good ion conductivity in anion exchange membranes.
[0009] Furthermore, the piperidinium cation is susceptible to OH - Attack, poor alkaline stability, resulting in a short service life of the membrane, the ether bond can attract OH to a certain extent - Therefore, by introducing a side chain containing a phenyl ether structure into the side chain, the OH group can be reduced to a certain extent. - The piperidinium cation is destroyed, and the phenyl group and the piperidinium cation can form a hydrophobic-hydrophilic phase separation structure, inducing the formation of microphase separation channels, thereby effectively enhancing the ion conductivity of the membrane. Finally, an anion exchange membrane with excellent performance is prepared by regulating the membrane structure. Summary of the invention
[0010] The object of the present invention is to provide a polynorbornene anion exchange membrane having both excellent alkaline stability and good ion conductivity, and a method for preparing the anion exchange membrane.
[0011] The polynorbornene anion exchange membrane of the present invention is a film made of a polymer having a structure shown in the following structural formula (I).
[0012]
[0013] Specifically, the polymer represented by the structural formula (I) of the present invention is a random copolymer composed of poly-5-norbornene-2-methylanisole structural units and poly-5-norbornene-2-methyl-N-methylpiperidinium bromide structural units, and the molar ratio of the structural units is m:n = (0.5-1):1.
[0014] More specifically, the polymer represented by structural formula (I) of the present invention is a quaternized polymer obtained by completely quaternizing a polynorbornene precursor composed of a poly-5-norbornene-2-methylanisole structural unit and a poly-2-bromomethyl-5-norbornene structural unit using N-methylpiperidine.
[0015] The polymer used to constitute the polynorbornene anion exchange membrane of the present invention adopts a polynorbornene main chain structure, so that the formed membrane can have good dimensional stability. Furthermore, by introducing ether bonds and phenyl large steric groups on the side chains of the polymer, the alkaline stability of the piperidine cation is improved, so that the membrane has high ion conductivity and good dimensional stability, thereby obtaining an anion exchange membrane with both excellent alkaline stability and good ion conductivity.
[0016] Furthermore, the present invention also provides a method for preparing the polynorbornene anion exchange membrane, the method comprising:
[0017] 1) Under inert protection, 5-norbornene-2-methanol and benzyl bromide are reacted in an N,N-diisopropylethylamine solvent system to prepare 5-norbornene-2-methylanisole;
[0018] 2) Using 5-norbornene-2-methylanisole and 2-bromomethyl-5-norbornene as monomers, a ring-opening metathesis polymerization reaction is carried out in an anhydrous dichloromethane solvent system in the presence of a Grubbs 3rd catalyst to obtain a polynorbornene precursor;
[0019] 3) dissolving the polynorbornene precursor in toluene and carrying out quaternization reaction with N-methylpiperidine to obtain a polymer having a structure shown in structural formula (I);
[0020] 4) Forming a polymer having a structure represented by structural formula (I) into a film to prepare a polynorbornene anion exchange membrane.
[0021] Specifically, 5-norbornene-2-methanol and benzyl bromide are dissolved in N,N-diisopropylethylamine, and heated to 150-155° C. for reflux reaction to prepare 5-norbornene-2-methylanisole.
[0022] More specifically, the molar ratio of 5-norbornene-2-methanol to benzyl bromide in the reflux reaction is 1:1.1-1.2.
[0023] Furthermore, the reaction time of the reflux reaction is 2 to 3 hours.
[0024] The reaction product obtained after the reflux reaction is completed is washed with ethyl acetate and deionized water in sequence, and then dried to obtain a crude product of 5-norbornene-2-methylanisole.
[0025] Furthermore, the present invention adopts column chromatography, uses petroleum ether as an eluent, and performs column chromatography separation and purification treatment on the above-obtained 5-norbornene-2-methylanisole crude product, and finally obtains a colorless 5-norbornene-2-methylanisole oily substance.
[0026] Wherein, the ring-opening metathesis polymerization reaction time is 1 to 2 hours.
[0027] The invention precipitates the reaction product polynorbornene precursor by adding methanol into the ring-opening metathesis polymerization reaction system.
[0028] Preferably, the volume of methanol added is not less than 10 times the volume of anhydrous dichloromethane.
[0029] Wherein, the quaternization reaction is carried out under reflux conditions at 60-70°C.
[0030] Furthermore, the quaternization reaction time is preferably 18 to 24 hours.
[0031] Specifically, the present invention prepares the polynorbornene anion exchange membrane by laying the quaternization reaction product under vacuum conditions at 80° C. for 24 hours, drying the solvent and unreacted N-methylpiperidine.
[0032] The present invention successfully synthesizes a novel polymer having excellent alkaline stability and OH by introducing a rigid side chain containing an ether bond and a phenyl group and a piperidinium cation into the side chain of a norbornene polymer. - Conductivity of polynorbornene-based anion exchange membranes.
[0033] The polynorbornene anion exchange membrane of the present invention has simple preparation method, low cost, excellent electrochemical performance and broad application prospects.
[0034] Specifically, the polynorbornene-based anion exchange membrane of the present invention can be used in alkaline fuel cells and water electrolysis devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the nuclear magnetic resonance hydrogen spectrum of polynorbornene anion exchange membrane (NAEM).
[0036] Figure 2 It is the IEC comparison curve of NAEM membrane.
[0037] Figure 3 It is a comparison curve of the swelling ratio of NAEM membrane.
[0038] Figure 4 It is a comparison curve of water absorption of NAEM membrane.
[0039] Figure 5 It is a comparison chart of tensile strength and elongation at break of NAEM membrane.
[0040] Figure 6 This is the relationship curve between the ionic conductivity and temperature of the NAEM membrane. Implementation
[0041] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0042] The production processes, experimental methods or detection methods involved in the embodiments of the present invention, unless otherwise specified, are all conventional methods in the prior art, and their names and / or abbreviations are all conventional names in the field, and are very clear and definite in the relevant application fields. Technical personnel in the field can understand the conventional process steps based on the names and apply the corresponding equipment, and implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0043] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example
[0044] Example 1
[0045] Under argon protection, 5-norbornene-2-methanol (1.24 g, 10 mmol) and benzyl bromide (1.929 g, 11 mmol) were dissolved in N,N-diisopropylethylamine (1.548 g, 12 mmol) and reacted at 150°C for 3 h.
[0046] The reaction product was cooled to room temperature, and the organic layer was washed with ethyl acetate and water respectively, and then purified by chromatography column using petroleum ether as eluent to prepare 5-norbornene-2-methylanisole.
[0047] 5-Norbornene-2-methylanisole (0.214 g, 1 mmol) and 2-bromomethyl-5-norbornene (0.187 g, 1 mmol) were dissolved in 15 ml of dry dichloromethane, and the solution was degassed to be anhydrous and oxygen-free. The third-generation Grubbs catalyst (6.9 mg) was added, and the solution was degassed again. The reaction was carried out at 40°C for 2 h to obtain a light yellow solution. The reaction solution was poured into methanol to precipitate a white flocculent precipitate of a polynorbornene precursor.
[0048] The polynorbornene precursor precipitate was filtered out, added into 10 ml of toluene and treated with ultrasound, and then N-methylpiperidine (0.0987 g, 1 mmol) was added and reacted at 60° C. for 24 h.
[0049] The reaction product was poured into a culture dish and dried at 80° C. to prepare an anion exchange membrane, which was designated as NAEM3.
[0050] The prepared anion exchange membrane was analyzed by nuclear magnetic resonance and the results showed that Figure 1 The hydrogen spectrum is shown in Figure 1. The chemical shift and integration ratio of hydrogen atoms in the spectrum are consistent with those of the target product.
[0051] Example 2
[0052] Under argon protection, 5-norbornene-2-methanol (1.24 g, 10 mmol) and benzyl bromide (2.104 g, 12 mmol) were dissolved in N,N-diisopropylethylamine (1.548 g, 12 mmol) and reacted at 150°C for 2 h.
[0053] The reaction product was cooled to room temperature, and the organic layer was washed with ethyl acetate and water respectively, and then purified by chromatography column using petroleum ether as eluent to prepare 5-norbornene-2-methylanisole.
[0054] 5-Norbornene-2-methylanisole (0.214 g, 1 mmol) and 2-bromomethyl-5-norbornene (0.2057 g, 1.1 mmol) were dissolved in 15 ml of dry dichloromethane, and the solution was degassed to be anhydrous and oxygen-free. The third-generation Grubbs catalyst (6.9 mg) was added, and the solution was degassed again. The reaction was carried out at 40°C for 1 hour to obtain a light yellow solution. The reaction solution was poured into methanol to precipitate a white flocculent precipitate of a polynorbornene precursor.
[0055] The polynorbornene precursor precipitate was filtered out, added into 10 ml of toluene and treated with ultrasound, and then N-methylpiperidine (0.1086 g, 1.1 mmol) was added and reacted at 60° C. for 20 h.
[0056] The reaction product was poured into a culture dish and dried at 80° C. to prepare an anion exchange membrane.
[0057] Example 3
[0058] Under argon protection, 5-norbornene-2-methanol (1.24 g, 10 mmol) and benzyl bromide (1.929 g, 11 mmol) were dissolved in N,N-diisopropylethylamine (1.548 g, 12 mmol) and reacted at 150°C for 2 h.
[0059] The reaction product was cooled to room temperature, and the organic layer was washed with ethyl acetate and water respectively, and then purified by chromatography column using petroleum ether as eluent to prepare 5-norbornene-2-methylanisole.
[0060] 5-Norbornene-2-methylanisole (0.214 g, 1 mmol) and 2-bromomethyl-5-norbornene (0.187 g, 1 mmol) were dissolved in 15 ml of dry dichloromethane, and the solution was degassed to be anhydrous and oxygen-free. The third-generation Grubbs catalyst (6.9 mg) was added, and the solution was degassed again. The reaction was carried out at 40°C for 2 h to obtain a light yellow solution. The reaction solution was poured into methanol to precipitate a white flocculent precipitate of a polynorbornene precursor.
[0061] The polynorbornene precursor precipitate was filtered out, added into 10 ml of toluene and treated with ultrasound, and then N-methylpiperidine (0.1185 g, 1.2 mmol) was added and reacted at 60° C. for 18 h.
[0062] The reaction product was poured into a culture dish and dried at 80° C. to prepare an anion exchange membrane.
[0063] Comparison example 1.
[0064] Except that the amount of N-methylpiperidine added was reduced to 0.0493 g (0.5 mmol), the other preparation processes were exactly the same as those in Example 1, and an anion exchange membrane NAEM1 was prepared.
[0065] Comparison example 2.
[0066] Except that the amount of N-methylpiperidine added was reduced to 0.074 g (0.75 mmol), the other preparation processes were exactly the same as those in Example 1, and anion exchange membrane NAEM2 was prepared.
[0067] The membrane properties of the anion exchange membrane NAEM3 prepared in Example 1 were tested and compared with the commercial Sustainion X37 anion exchange membrane (CAEM) and control examples 1 and 2. The results are as follows: Figure 2-6 shown.
[0068] like Figure 2 As shown, as the degree of quaternization of the NAEM membrane of the present invention increases, its IEC value shows a trend of gradually increasing, and the actual test results are consistent with the expected target. In the case of complete quaternization, the IEC value of NAEM3 can reach 2.15mmol / g, which is much higher than the commercial CAEM membrane.
[0069] On the other hand, the water absorption and swelling rate of NAEM membrane also showed a corresponding trend, but depending on the stability of the norbornene main chain structure and the interaction between the phenyl ether side chain and the piperidinium cation, the water absorption and swelling rate of NAEM membrane were much lower than those of CAEM membrane, such as Figure 3 , 4 The experimental results show that the anion exchange membrane prepared by the present invention has good dimensional stability, so that the membrane can maintain its morphological structure in a more severe environment.
[0070] Furthermore, from Figure 5 It can be seen from the mechanical properties test results that the new NAEM membrane containing phenyl ether structure side chains of the present invention exhibits better mechanical properties than the commercial CAEM membrane. This depends on the introduction of phenyl ether structure on the side chain. The effect of the rigid group enables the membrane to have better tensile strength and elongation at break.
[0071] Figure 6 The ionic conductivity of the NAEM membrane tested in pure water electrolyte is given. At 20-80°C, with the increasing degree of quaternization, the ionic conductivity of the NAEM membrane also increases. The fully quaternized NAEM3 membrane can reach a maximum of 91.2ms / cm, which is about 32ms / cm higher than the ionic conductivity of 58.9ms / cm of the CAEM membrane. This is attributed to the increase in the quaternization ratio and the hydrophilic-hydrophobic microphase separation structure formed between the side chain structure of the phenyl ether and the ammonium cation, which enhances the ion transport effect.
[0072] The above results prove that the NAEM membrane containing phenyl ether side chains and piperidinium cation structures of the present invention can solve the problem of poor dimensional stability of anion exchange membranes due to excessively high IEC to a certain extent. At the same time, the piperidinium cation and the phenyl ether structure can form a microphase separation structure, further enhancing the ionic conductivity, thereby improving battery performance.
[0073] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A polynorbornene anion exchange membrane, which is a film made of a polymer having a structure represented by the following structural formula (I): ; in, The polymer represented by the structural formula (I) is a random copolymer composed of poly-5-norbornene-2-methylanisole structural units and poly-5-norbornene-2-methyl-N-methylpiperidinium bromide structural units, and the molar ratio of the structural units is m:n = (0.5-1):
1.
2. The method for preparing the polynorbornene anion exchange membrane according to claim 1, comprising: 1) Under inert protection, 5-norbornene-2-methanol and benzyl bromide are reacted in an N,N-diisopropylethylamine solvent system to prepare 5-norbornene-2-methylanisole; 2) Using 5-norbornene-2-methylanisole and 2-bromomethyl-5-norbornene as monomers, a ring-opening metathesis polymerization reaction is carried out in an anhydrous dichloromethane solvent system in the presence of a Grubbs 3rd catalyst to obtain a polynorbornene precursor; 3) dissolving the polynorbornene precursor in toluene and carrying out quaternization reaction with N-methylpiperidine to obtain a polymer having a structure shown in structural formula (I); 4) Forming a polymer having a structure represented by structural formula (I) into a film to prepare a polynorbornene anion exchange membrane.
3. The preparation method according to claim 2, characterized in that 5-norbornene-2-methanol and benzyl bromide are dissolved in N,N-diisopropylethylamine, and the mixture is heated to 150-155° C. for reflux reaction to prepare 5-norbornene-2-methylanisole.
4. The preparation method according to claim 2 or 3, characterized in that The molar ratio of 5-norbornene-2-methanol to benzyl bromide is 1:1.1-1.
2.
5. The preparation method according to claim 3, characterized in that The reflux reaction time is 2 to 3 hours.
6. The preparation method according to claim 2, characterized in that The ring-opening metathesis polymerization reaction time is 1 to 2 hours.
7. The preparation method according to claim 2, characterized in that The quaternization reaction is carried out under reflux conditions at 60-70° C. for 18-24 hours.
8. The preparation method according to claim 2, characterized in that The quaternization reaction product was laid as a membrane and then placed under vacuum at 80° C. for 24 hours to prepare the polynorbornene anion exchange membrane.
9. Use of the polynorbornene anion exchange membrane according to claim 1 in the preparation of an alkaline fuel cell or a water electrolysis device.
Citation Information
Patent Citations
Proton-conducting membrane and its use
CN102047479A
Cross-linked polymer and anion exchange membrane based on same
CN111518263A